Left Atrial-Esophageal Fistula Repair after Radiofrequency Catheter Ablation for Atrial Fibrillation - Velotta, Jeffrey B.; Vasquez, Charles R.; Bolman, Ralph M.; Dasilva, Marcelo C. (The Thoracic and Cardiovascular Surgeon Reports, 2013)
Left atrial-esophageal fistula (LAEF) is a rare complication of radiofrequency ablation (RFA) procedures undertaken for atrial fibrillation (AF). This complication is associated with significant morbidity and mortality. Currently, there is no clear consensus on the appropriate management strategy. We report a case of a LAEF that developed in a patient 2 weeks after RFA for medication refractory AF. The patient underwent successful repair of the fistula through a left posterolateral thoracotomy, wherein the esophageal and atrial lesions were repaired primarily with an intercostal muscle flap and bovine pericardial patch to reinforce and prevent recurrence.
Keywords: ablative therapy; atrial fibrillation; atrial-esophageal; esophageal surgery; thoracotomy